Some fixed point theorems via combination of weak contraction and Caristi contractive mapping - Roy, Kushal; Panja, Sayantan; Saha, Mantu; Mitrović, Zoran D. (Annales Mathematicae Silesianae, 2021)
In this paper we introduce some new types of contractive mappings by combining Caristi contraction, Ciric-quasi contraction and weak contraction in the framework of a metric space. We prove some fixed point theorems for such type of mappings over complete metric spaces with the help of '-diminishing property. Some examples are given in strengthening the hypothesis of our established theorems.